DEVELOPMENT OF RISDA SIMULATION BASED LEARNING MODEL FOR INDUSTRIAL ELECTRONICS EDUCATION - Phacharoen, Ekkaphan; Akatimagool, Somsak (Journal of Education and Innovation, 2024)
This research presents the development of the RISDA simulation-based learning model for industrial electronics education. The research methodology begins with a survey of needs from stakeholders based on the requirements of graduate’s competencies, then develops a simulation-based learning and teaching model called the RISDA model. The RISDA model comprises of 5 stages: Recall, Information, Simulation, Discussion, and Assessment. The research tools such as teacher manuals of industrial electronics, learning activity plans, simulation-based teaching media and objective test were constructed. Then, it was used to implement with a sample of 20 undergraduate students, program in industrial technology, Burapha University. The results showed that 1) the research tools created were appropriate at a high level ( = 4.46, SD = 0.57), 2) the developed RISDA model was effective according to the Meguigans standard (the value was 1.01), 3) students’ learning achievement after learning was higher than before learning at a statistical significance at the .05 level, and 4) learners who had learned using the RISDA model had their satisfaction at a high level ( = 4.48, SD = 0.71). The developed RISDA model can promote learners’ competencies in line with 21st century learning skills and appropriately accommodate the needs of the workplace.